Workplace‐based assessments in Foundation Programme training: do trainees in difficulty use them differently?. Issue 3 (8th February 2013) - Mitchell, Colin; Bhat, Sarita; Herbert, Anne; Baker, Paul
<x xml:space="preserve">Abstract</x> Context Trainee‐led workplace‐based assessment (WPBA) is increasingly used in postgraduate medical training. Trainees in difficulty are known to behave differently from their peers; these differences may be reflected in their use of WPBAs and may give new insights into the behaviour and assessment of struggling trainees. Methods Data were extracted for 76 115 assessments, completed by 1900 UK Foundation Programme (FP) trainees. Of these 1900 trainees, 95 (5%) were FP trainees in difficulty (FTiDs). We analysed aspects of the use of WPBAs, using multiple logistic regressions, to compare the behaviours of FTiDs with those of their peers. Results Of 48 possible comparisons, only two (i.e. the rate expected to occur by chance) showed statistically significant differences: relative to their peers, FTiDs were more likely to choose nurse assessors in direct observations of procedural skills (odds ratio [OR] 7.05, 95% confidence interval [CI] 1.23–40.43) and more likely to choose non‐clinical assessors for assessments using the mini‐peer assessment tool (OR 30.44, 95% CI 1.34–689.29). Conclusions Key features of assessor choice for FTiDs are familiarity and likelihood of receiving a positive assessment. This analysis has not demonstrated that FTiDs use WPBAs any differently from their peers who are not in difficulty, although it does suggest associations and trends that require further exploration. These null results are interesting and raise hypotheses for prospective confirmation or disproof, and for further qualitative work investigating how struggling trainees use WPBAs in order to guide the future implementation of WPBAs in postgraduate training.